A Case of Grover's Disease Secondary to Brodalumab Therapy for Psoriasis. Issue 1 (January 2021) - Muzumdar, Sonal; Radfar, Arash; Payette, Michael
Background: Grover's disease has been associated with a number of medications including sulfadoxine-pyrimethamine, recombinant interleukin (IL)-4, ipilimumab, and BRAF inhibitors. To our knowledge, Grover's disease has not been reported in association with interleukin-17 inhibitors. Case Description: A 47-year-old female with plaque psoriasis developed Grover's disease 3 months following initiation of brodalumab. Discontinuation of brodalumab and initiation of certolizumab pegol and methotrexate led to resolution of her rash. Conclusion: This case highlights Grover's disease as a potential adverse effect of brodalumab therapy. In patients who develop Grover's disease with brodalumab, modification of therapy may be considered due to the bothersome nature of the rash.